1985
DOI: 10.1007/bf02388765
|View full text |Cite
|
Sign up to set email alerts
|

Absence of prognostic significance of skeletal involvement in acute lymphocytic leukemia and non-Hodgkin lymphoma in children

Abstract: Over a period of 6 years 88 children with acute lymphocytic leukemia and malignant non-Hodgkin lymphoma were treated according to the West-Berlin protocol. In 72 children skeletal surveys were performed initially and these showed leukemic bone changes in 31 patients. Follow-up was obtained in 70 patients for up to 8 years after diagnosis: 20 of these patients died and of these 8 showed initial skeletal involvement. In 17 children relapses occurred and 10 of them had bone lesions at first presentation. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…A recent study found that children with severe skeletal involvement had a better prognosis than children without skeletal involvement [43]. This is in opposition to previous investigators, who had found that skeletal involvement connoted a poorer prognosis [44,45] or no prognostic significance [46][47][48].…”
Section: X-raysmentioning
confidence: 73%
“…A recent study found that children with severe skeletal involvement had a better prognosis than children without skeletal involvement [43]. This is in opposition to previous investigators, who had found that skeletal involvement connoted a poorer prognosis [44,45] or no prognostic significance [46][47][48].…”
Section: X-raysmentioning
confidence: 73%
“…Complete remission of ALL was induced in all patients, and symptoms of vertebral compression fractures abated following antileukemia therapy. Appell RG et al however did not fi nd any prognostic signifi cance of skeletal involvement in their study of 88 patients of pediatric ALL and NHL [8]. In contrast, G Masera et al reported that children with multiple bone lesions are associated with poor prognosis [9].…”
Section: Discussionmentioning
confidence: 91%
“…Ayrıca bu hastaların %41-70'inde tanı anında radyolojik deği-şiklikler görülmektedir. Osteolitik lezyonlar %11-90 oranında, metafizeal bandlar %7-88 oranında, periost reaksiyonu %2-50, diffüz osteoporoz %16-41 ve osteoskleroz %3-31 oranında bildirilmiştir (6) . Makalemizde septik artrit tablosu ile başvuran ve takibinde periost reaksiyonu görülerek ALL tanısı konulan olgu sunulmuştur.…”
Section: Introductionunclassified